2021
DOI: 10.20944/preprints202106.0581.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melatonin as an Antioxidant and Immunomodulator in Atopic Dermatitis–A New Look on an Old Story–A Review

Abstract: Atopic dermatitis (AD) is common inflammatory dermatosis, typically with chronic and recurrent course, which significantly reduces the quality of life. Sleep disturbances are considered to be remarkably burdensome ailments in the patients with AD, and are routinely included during assessment of disease severity. Therefore, endogenous substances engaged in the control of circadian rhythms might be important in pathogenesis of AD and, possibly, be used as biomarkers of disease severity or even in development of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…The correlation between SCORAD and melatonin levels has not been widely studied. 8 A Turkish study by Uysal et al in 2016 reported a significant negative correlation between SCORAD in severe AD and melatonin levels, while in mild-moderate cases, a non-significant correlation was found. 31 In this study, all participants in the case group had moderate AD, thus data on the correlation between melatonin levels and SCORAD in severe AD were not obtained.…”
Section: This Ismentioning
confidence: 97%
See 4 more Smart Citations
“…The correlation between SCORAD and melatonin levels has not been widely studied. 8 A Turkish study by Uysal et al in 2016 reported a significant negative correlation between SCORAD in severe AD and melatonin levels, while in mild-moderate cases, a non-significant correlation was found. 31 In this study, all participants in the case group had moderate AD, thus data on the correlation between melatonin levels and SCORAD in severe AD were not obtained.…”
Section: This Ismentioning
confidence: 97%
“…7 Sleep loss is an undisputed feature of AD, which must be taken into account when in assessing disease severity using the Scoring Atopic Dermatitis (SCORAD) scale. 8 Sleep disturbances among AD patients is prevalent and frequently reported, especially in children with moderate-severe AD. 8 Although the main symptoms of AD, such as excessive itch and the consequent scratching, seem to sufficiently explain the abnormal sleep pattern seen among patients, previous studies have reported that children with AD in remission experience significant sleep disturbances not related to scratching.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations